Educação do campo: entre o fazer pedagógico e o saber popular - CASTRO, Andrea Silva de (2022)
In this dissertation, we carry out a study on experiences of local culture and popular knowledge, focusing on education for/in the countryside and teacher pedagogical practices. Our aim was to present contributions to Rural Education at the Enock Alves Bezerra Municipal School. Thus, we sought to understand the educators' conceptions about education; we investigated local culture valorization/depreciation; we built reflections on autonomy in teaching work. In the methodological field, we carried out an action research with the participation of seven subjects, that is, five male teachers, a female teacher and the school principal from Enock Alves Bezerra Municipal School. This is a qualitative study with contributions from historical and dialectical materialism. For data construction, we used observations, field log, recordings, document analysis and culture circles. Then, we organized the themes, subthemes, words and generating expressions. In the analysis of the constructed data and in the considerations, we sought to reflect on the situation-problem challenge. Among the results, we found out that educators experience an urban centric teaching and the community's culture occupies little space in pedagogical practices. However, through dialogic work, it was possible to reflect on the issue of autonomy, and these dialogues opened space to the raising of ideas for new approaches about the community’s culture and knowledge through the pedagogical practice applied by teachers.